Analisa Profitabilitas dan Likuiditas pada PT Bank Capital Indonesia Tbk Periode 2019-2023 - istiqomah, azizatul; Aisyah, Esy Nur (Maliki Interdisciplinary Journal, 2025)
This study aims to assess the financial performance of PT. Bank Capital Indonesia for the period 2019-2023 using a comparative descriptive method that focuses on the analysis of annual financial statements through financial ratios, such as ROA, ROE, BOPO, and LDR. The data analyzed includes the company’s financial position report and profit and loss report. The results of the study indicate that PT. Bank Capital Indonesia has not met the financial standards set by Bank Indonesia. The company’s ROA and ROE are still low, indicating low profitability against assets and equity. In addition, the high BOPO ratio reflects less than optimal operational efficiency, while the very low LDR over the past few years indicates that the utilization of third-party funds has not been maximized in credit distribution. To improve performance, the company needs to implement strategies to increase profitability, operational cost efficiency, and credit optimization. This study provides an in-depth overview of the challenges and opportunities for improving the bank’s financial performance in the future.